(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The Importance of a Multifaceted Approach in Language Teaching The teaching of English as a second language has undergone significant transformation over the years. Traditional methods such as grammar-translation or direct method instruction have given way to more diverse approaches. In today’s globalized world, the ability to speak and understand English has become increasingly important for communication, career opportunities, and education. However, no single teaching method can cater to all learners’ needs. Every student is unique, with different learning preferences, backgrounds, and motivations. As such, effective language instruction requires flexibility and adaptability. One of the most successful approaches to teaching English is a mixed-methods approach, where different teaching methods and strategies are combined to meet the varied needs of students. This blend allows teachers to create a dynamic and engaging learning environment that fosters communication, fluency, and a deep understanding of English.